2016
DOI: 10.1158/1078-0432.ccr-15-0916
|View full text |Cite
|
Sign up to set email alerts
|

A Supplemented High-Fat Low-Carbohydrate Diet for the Treatment of Glioblastoma

Abstract: Purpose: Dysregulated energetics coupled with uncontrolled proliferation has become a hallmark of cancer, leading to increased interest in metabolic therapies. Glioblastoma (GB) is highly malignant, very metabolically active, and typically resistant to current therapies. Dietary treatment options based on glucose deprivation have been explored using a restrictive ketogenic diet (KD), with positive anticancer reports. However, negative side effects and a lack of palatability make the KD difficult to implement i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 60 publications
(69 reference statements)
3
81
0
2
Order By: Relevance
“…A similar synergistic effect was observed between KD and temozolomide in the GL-261 model [84]. Comparable effects of KDs on tumor growth and survival time have also been shown in glioma derived mouse models of metastatic cancer and in patient-derived GBM subcutaneous and orthotopic implantation models [85,86]. These and other studies suggest that KDs induce a metabolic shift in malignant brain tissue towards a pro-apoptotic, anti-angiogenic, anti-invasive and anti-inflammatory state accompanied by a marked reduction in tumor growth in vivo [70] via mechanisms that include:

Reduction in blood glucose and insulin growth factor-1 levels [79];

Attenuated insulin activated Akt/mTOR and Ras/mitogen-activated protein kinase (MAPK) signaling pathways [87,88];

Induction of genes involved in oxidative stress protection and elimination of ROS through histone deactylase inhibition and altered expression of genes related to angiogenesis, vascular remodeling, invasion potential and the hypoxic response [38,82,84];

Enhanced cytotoxic T cell anti-tumor immunity [89]; and

Reduced inflammation via ketone body inhibition of the NLRP3 inflammasome and a reduction in other circulating inflammatory markers [43,90].

…”
Section: Kds In the Management Of Adult Malignant Gliomassupporting
confidence: 53%
“…A similar synergistic effect was observed between KD and temozolomide in the GL-261 model [84]. Comparable effects of KDs on tumor growth and survival time have also been shown in glioma derived mouse models of metastatic cancer and in patient-derived GBM subcutaneous and orthotopic implantation models [85,86]. These and other studies suggest that KDs induce a metabolic shift in malignant brain tissue towards a pro-apoptotic, anti-angiogenic, anti-invasive and anti-inflammatory state accompanied by a marked reduction in tumor growth in vivo [70] via mechanisms that include:

Reduction in blood glucose and insulin growth factor-1 levels [79];

Attenuated insulin activated Akt/mTOR and Ras/mitogen-activated protein kinase (MAPK) signaling pathways [87,88];

Induction of genes involved in oxidative stress protection and elimination of ROS through histone deactylase inhibition and altered expression of genes related to angiogenesis, vascular remodeling, invasion potential and the hypoxic response [38,82,84];

Enhanced cytotoxic T cell anti-tumor immunity [89]; and

Reduced inflammation via ketone body inhibition of the NLRP3 inflammasome and a reduction in other circulating inflammatory markers [43,90].

…”
Section: Kds In the Management Of Adult Malignant Gliomassupporting
confidence: 53%
“…Maintaining mitochondrial OxPhos activities may confer SCCs broader metabolic capacities beyond those of aerobic glycolysis. We had previously shown that GBM cells were sensitive to glucose deprivation (Martuscello et al , ) and next examined whether GBM SCCs and FCCs displayed the same glucose dependencies. We tested the response of SCCs and FCCs to high (500 mg/dl) or lowered/physiological (90–110 mg/dl) glucose levels in normoxic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that activation of anaerobic metabolism in the rapidly growing brain cancer parenchyma may induce CSCs in an autologous fashion and that targeting the production of low pH generating metabolites may indirectly inhibit CSC development. Another study demonstrated that high‐lipid growth conditions with limited amounts of carbohydrates impairs GBM CSCs most probably due to suppressed mTOR signaling . This observation provides a possible molecular link between dietary status of a patient and their CSC condition.…”
Section: Environmental Stress and Therapeutic Insults Alter Csc Metabmentioning
confidence: 92%